Bercerita dengan Lagu dan Gerak - Purnanto, Arif Wiyat; Anisah, Anisah (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2017)
The purpose of this research is to improve the ability of storytelling in third grade elementary school and also the researcher intends to improve learning in the aspect of speaking competence narrating personal experience. The method of this research is Tell Story With Sing And Motion. The results of this study were : (1) Introducing the Tell story with sing and motion method in children; (2) Train children to socialize with their friends through personal experiences; (3) Grow courage and confidence in children through storytelling activities; (4) Improving the creativity of children in conveying personal experiences (5) Reminding children of the importance of learning from an experience (6) Supporting factors; (7) Inhibiting factors. Based on the discussion of the research results, the conclusions obtained are: Tell Story with Sing and Motion method can improve the ability to tell the children in grade III SD.